Dispersive liquid‐liquid microextraction for four phenolic environmental estrogens in water samples followed by determination using capillary electrophoresis. Issue 19 (17th May 2016) - Liu, Junying; Lu, Wenhui; Liu, Huitao; Wu, Xiaqing; Li, Jinhua; Chen, Lingxin
Abstract : Dispersive liquid‐liquid microextraction (DLLME) coupled with CE was successfully developed for simultaneous determination of four types of phenolic environmental estrogens (PEEs), namely hexestrol (HS), bisphenol A (BPA), diethylstilbestrol (DES) and dienestrol (DS). Several parameters affecting DLLME and CE conditions were systematically investigated including the type and volume of extraction solvent and dispersive solvent, extraction time, salt, pH value, surfactant, buffer solution and so on. Under the optimal conditions, DLLME‐CE exhibited strong enrichment ability, presenting high enrichment factors of 467, 241, 367 and 362 for HS, BPA, DES and DS, respectively, as well as low detection limits of 0.3, 0.6, 0.6 and 0.3 μg/L, respectively. Excellent linearity was achieved in the range of 2.0–150 μg/L for HS and DS, and 4.0–300 μg/L for BPA and DES, with correlation coefficients R >0.9983. Recoveries ranging from 70.4 to 108.1% were obtained with tap water, lake water and seawater samples spiked at three concentration levels and the relative standard deviations (RSDs, for n = 5) were 2.1–9.7%. This DLLME‐CE method with high selectivity and sensitivity, high stability, simplicity, cost‐effectiveness, eco‐friendliness was proved potentially applicable for the rapid and simultaneous determination of PEEs in complicated water samples.